2020
DOI: 10.1016/j.omtn.2020.07.019
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: HOTAIR Accelerates Dyskinesia in a MPTP-Lesioned Mouse Model of PD via SSTR1 Methylation-Mediated ERK1/2 Axis

Abstract: Homeobox transcript antisense RNA (HOTAIR), has been associated with neuroprotective effects in Parkinson’s disease (PD). However, the underlying mechanisms still remain unclear. Hence, this present study attempted to clarify the functional relevance of HOTAIR in PD. We established an in vivo mouse model of PD using 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and an in vitro cell model of PD by treating dopaminergic neuron MN9D cells with 1-methyl-4-phenylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…also uncovered that abnormal activation of ERK could increase the radioresistance of liver cancer cells [ 39 ]. In addition, overexpression of HOTAIR has been reported to accelerate dyskinesia and facilitate dopaminergic neuron apoptosis in a Parkinson’s disease mouse model via activation of the ERK1/2 axis [ 59 ]. Another study has shown that HOTAIR depletion can promote apoptosis of lymphoma cells via inactivation of the ERK signaling pathway [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…also uncovered that abnormal activation of ERK could increase the radioresistance of liver cancer cells [ 39 ]. In addition, overexpression of HOTAIR has been reported to accelerate dyskinesia and facilitate dopaminergic neuron apoptosis in a Parkinson’s disease mouse model via activation of the ERK1/2 axis [ 59 ]. Another study has shown that HOTAIR depletion can promote apoptosis of lymphoma cells via inactivation of the ERK signaling pathway [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a PD cell model, HOTAIR bound to the promoter region of somatostatin receptor 1 (SSTR1), leading to increased methylation of SSTR1 by recruiting DNA methyltransferases. Notably, in a MPTP-induced PD mouse model, overexpressed HOTAIR stimulated DNA methylation of SSTR1 to reduce SSTR1 expression, thereby accelerating dyskinesia and facilitating dopaminergic neuron apoptosis ( Cai et al, 2020 ). LRRK2 gene mutations have been widely recognized as the most common cause of dominantly inherited PD and one of the risk factors for sporadic PD ( Tolosa et al, 2020 ).…”
Section: Hotair Involvement In Pathogenesis Of Central Nervous System...mentioning
confidence: 99%
“…LncRNA HOTAIR has been broadly examined in numerous investigations. In in vivo and in vitro Parkinson's disease models, the expression of HOTAIR is enhanced and its' overexpression aggravates dyskinesia, which indicates that HOTAIR may participate in neuro-degenerative disorders [3].…”
Section: Introductionmentioning
confidence: 99%